Correlation between the Orientation of Cross-Field Axes of Small-Scale Anisotropic Irregularities in Midlatitude Ionosphere and Drift Direction in the F Region - Valery A. Panchenko; Viktor A. Telegin; Natalia Yu. Romanova (Известия высших учебных заведений России: Радиоэлектроника, 2019)
Introduction. It has been previously reported that small-scale irregularities (SSI) in the polar ionosphere are elongated along the magnetic field and anisotropic in its cross-field direction. At the same time, the largest of the SSI cross-field axes tends to orient along the SSI drift direction. However, there is no evidence of direct correlations of SSI anisotropy and ionospheric drift directions in the middle latitudes. Objective. A direct comparison of the experimental data of SSI shape with motion parameters of irregularities was measured at the same place (Moscow) at the same time. Previously, experimentally obtained values of SSI cross-field anisotropy orientation in the midlatitude ionosphere were compared only with the neutral winds model. Materials and methods. A tomographic approach was used to determine SSI anisotropy parameters by processing radio scintillation signals during overfly by several navigation satellites emitting on frequencies of 150 MHz and 400 MHz. Estimations were obtained of the ratio between the ellipsoid axes and cross-field anisotropy orientations in the framework of the SSI model in a form of magnetic field-oriented ellipsoids with three different dimensions along and across the Earth's magnetic field. The parameters of irregularities were obtained by selecting model parameters at a time when the calculated logarithm dispersion of the satellite signals relative amplitude during orbit is the closest to the experimentally obtained curve. Estimations were obtained of the velocity and drift direction of medium-scale irregularities (MSI) by using DPS-4 ionosonde data acquired while decametre-wave radar studies of ionosphere from the Earth's surface. Simultaneous measurements of Doppler frequency shifts and incident angles of scattered waves allowed estimations of three components of the medium-scale irregularities drift velocity to be obtained. Results. There was evidence of a good correlation between the drift direction of medium-scale irregularities and cross-field anisotropy orientation of small-scale irregularities. The difference in the drift directions of MSI and in the orientation of the cross-field axes of SSI varied from 3 to 10 degrees (provided the spatial coincidence of the ionosphere regions where the measurements were carried out). Conclusion. In constructing a model of the radar backscattering signal in the HF band, the correlation between the cross-field anisotropy orientation of the elongated irregularities and their drift direction can be useful when there is a lack of information on ionospheric irregularities.